Litigating international law disputes : weighing the options - Klein,Natalie,Ed (Cambridge, 2014)
"Litigating International Law Disputes provides a fresh understanding of why states resort to international adjudication or arbitration to resolve international law disputes. A group of leading scholars and practitioners discern the reasons for the use of international litigation and other modes of dispute settlement by examining various substantive areas of international law (such as human rights, trade, environment, maritime boundaries, territorial sovereignty and investment law) as well as considering case studies from particular countries and regions. The chapters also canvass the roles of international lawyers, NGOs, and private actors, as well as the political dynamics of disputes, and identify emergent trends in dispute settlement for different areas of international law"--